The Importance of Work Balance: Mediation in The Relationship Between Jobs Stress, Workload, and Employee Job Satisfaction PT. Suri Adidaya Kapuas Kumai - Setyorini, Winarti (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Success in ones job is directly proportional to work life balance. This study aims to ascertain the significance of work-life balance in relation toting stress and heavy workload work with job satisfaction PT Suri Adidaya Kapuas Kumai employees. Therefore it is hopeful that the results of the study will be a significant benefit to human resource management of company to improve worker satisfaction and well-being. The research was based on quantitative and survey methodologies. PT Suri Adidaya Kapuas Kumai distributed questionnaires in order to gather information.. Since the sample size was the same as the number of representative workers, this sample size was randomly extracted and it was 35 employees. Work stress, workload, work balance, Job statisfaction parts of questionare were the sections designed to determine stress levels in the work. The data generated was processed using SMARTPLS. Results: The direct effects of job stress and of workload on work-life balance and of work-life balance impact on open to new experiences strokeLine [FtFt1] were significant. Job stress significantly influences job satisfaction, workload insignificant effects on contentment in one's work. Work stress moderates positively, work-life balance negative and work stress interactspositively and off course work stress negatively influences Job satisfaction. Consequently, these results provide a foundation for business management for managing the employee stress and workload for satisfactions in their job opportunities.